Effect of Service Quality on Outpatient Satisfaction at Wede Ar- Rachman Clinic in Bandar Lampung After Using a QR CODE-Based Patient Complaint Information System - Catur Yuda Pujiani; Sunarno Sunarno; Anggalia Wibasuri (Proceeding International Conference on Information Technology and Business, 2022)
Health clinic is a health service institution that provides health services. Health clinics have several types of services including medical services, medical support services, and also as a place for medics to gain medical education. Therefore, a health clinic must have good resources. Wede Ar-Rachman Clinic started implementing a barcode-based complaint information system since August 2022 as an evaluation material for the clinic. This study aims to determine how much influence service quality has on outpatient satisfaction at Wede Ar-Rachman Clinic in Bandar Lampung after using a QR CODE-based patient complaint information system. Two hundred of respondents have been taken using purposive sampling. In this study, data analysis uses the Structural Equation Model (SEM). Based on the results of data analysis, it can be concluded that Service Quality has an effect on patient satisfaction after using the QR Code system.Keywords—service quality, patient satisfaction, information system, QR Code